Four cases of late onset metachromatic leucodystrophy in a family: clinical, biochemical and neuropathological studies. Issue 12 (December 1986) - Alves, D; Pires, M M; Guimarães, A; Miranda, M C
Abstract : Four cases of familial metachromatic leucodystrophy are described: the age of onset ranged from 15 to 21 years. Mental deterioration was the earliest clinical sign to be noted and all progressed to severe dementia. The arylsulphatase activity in peripheral leucocytes of the patients was very low, 5 to 15 nmol/h/mg protein, moderately reduced in the heterozygote, 40 nmol/h/mg protein, compared with control values of 60-160 nmol/h/mg protein. Sural nerve biopsies in two cases showed perivascular macrophages filled with metachromatic material and electron microscopy showed typical inclusions in Schwann cell cytoplasm. Necropsy in one of the cases revealed severe demyelination mainly in the cerebral hemispheres with metachromatic material in macrophages and neurons.